The payment system benefits of high reserve balances - James Joseph McAndrews; Alexander Kroeger (Federal Reserve Bank of New York, 2016)
The policy measures taken since the financial crisis have greatly expanded the size of the Federal Reserve's balance sheet and have thus raised the level of aggregate bank reserves as well. Over the same period there has been a significant shift in the timing of payments made over the Federal Reserve's Fedwire Funds Service toward earlier settlement. This paper documents this timing change and presents regression results suggesting that the increase in overall reserve balances explains the vast majority of this development. The paper also discusses the benefits of high aggregate reserve balances for the robustness of the payment system and the potential implications for policy going forward.
Keywords: G20; G21; G28; 330; Fedwire; settlement liquidity; reserves; monetary policy implementation